2020
DOI: 10.1016/j.plabm.2020.e00186
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Sysmex-XN 2000 and Yumizen H2500 automated hematology analyzers

Abstract: A complete blood count is a highly automated laboratory test. The use of highly advanced measurement methods increases the accuracy and sensitivity of the determination of individual hematological parameters, especially in the case of white blood cells differentiation. Therefore, it is necessary to make comparative analyses, which involve performance of the analyzers used in daily work. The aim of the study was to indicate whether the results obtained using two compared analyzers show significant differences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…have previously compared the YH2500 to the Sysmex XN-2000 and concerning the WBC-diff, the results showed a significant difference on the eosinophil and immature granulocyte count. 12 They concluded that the different techniques used in the two analyzers may be the source of variability. However, the flagging performance of the two analyzers was not studied.…”
Section: Discussionmentioning
confidence: 99%
“…have previously compared the YH2500 to the Sysmex XN-2000 and concerning the WBC-diff, the results showed a significant difference on the eosinophil and immature granulocyte count. 12 They concluded that the different techniques used in the two analyzers may be the source of variability. However, the flagging performance of the two analyzers was not studied.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were collected as usual and submitted to automated processing in the Sysmex XN-1000 equipment and, after analyzing the results, selected for counting reticulocytes and their IRF in the same equipment, which uses fluorescent dyes as the technology that bind to the RNA of reticulocytes and IRF 16,17 .…”
Section: Methodsmentioning
confidence: 99%
“…Values between 25,000 and 85,000/mm³ were considered as reference values for the absolute reticulocyte count in people aged over 30 days of life. However, as there are no absolute reference values for the IRF in the literature, these were analyzed only as research parameters 17 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Yumizen H2500 mixes the samples at 360° to ensure their homogeneity. The analyzer capacity is 120 samples per hour and the sample volume needed for analysis is 110 μl [ 9 ].…”
Section: Methodsmentioning
confidence: 99%